Citizen science as a tool for understanding the silent dispersion of toadfish Opsanus beta (Goode and Bean, 1880). Issue 6 (27th March 2022) - Carvalho, Barbara Maichak de; Freitas, Matheus O.; Tomás, Acácio R. G.; Caires, Rodrigo; Charvet, Patricia; Vitule, Jean
Abstract: Citizen science is an excellent tool in studies of the spatial distribution of non‐native species. In Brazil, Opsanus beta has recently been introduced. Studies indicate the occurrence of this species in five estuaries off the Brazilian coast (Guanabara Bay, Sepetiba Bay, Santos Bay, Paranaguá Estuarine Complex and Guaratuba Bay). The present study aims to understand the dispersion of this species on the Brazilian coast through citizen science. Between January and May 2021, information about O. beta was weekly posted in 32 recreational fishing Facebook groups. Sixty‐five fishers reported catches of O. beta in estuaries (Guanabara Bay, Sepetiba Bay, Santos Bay and Paranaguá Estuarine Complex). In addition, there were reports from other shallow areas outside adjacent estuaries (Bertioga and Peruíbe, in Sao Paulo State) and the first occurrence record for Laguna (Santa Catarina State), a southern estuarine zone (28° 29′ 45″ S to 48° 45′ 36″ W). In four estuaries along the Brazilian coast where O. beta was recorded, there are internal ports that trade with countries from the Gulf of Mexico and Caribbean Sea (species original range), indicating ballast water as a possible introduction route. In Laguna, the introduction may have occurred by maritime cabotage services. The reproductive capacity, the aquarists' interest, the absence of introduction policies aimed at this species and the cabotage fleet transportation may be factors that help further extend the dispersal of O. beta on the Brazilian coast.